Perubatan Islam: Analisis Perkembangan, Kesan, dan Permerkasaan di Malaysia - Muhammad Remy bin Othman; Sayidah Asma binti Basir; Khadher bin Ahmad; Khalijah binti Awang; Zulkifli bin Mohd Yusof (USIM Press, 2024)
VOL. 28 Page (25-47)